DIGITAL TRANSFORMATION AND ITS INFLUENCE ON GDP - Mićić, Ljubiša (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2017)
Digital transformation as integration of digital technology into business results in fundamental changes of way world does business, communicate and develops on national and international level. There is increase of high-tech public spending which is connected with increase of need for high-tech as well as importance and benefits that it brings to development of economy. This so called digital or high-tech sector is one of the strategic sectors in the leading world economies, starting from the US and the European Union. EU recognized it in strategic document “Europe 2020” which sees this sector as key factor in smart growth based on tech knowledge and innovation. Europe, especially western and northern Europe, is trying to keep its competitiveness in global tech arena with USA and fast developing countries such as China and India as well as Asian tech giants such are Japan, South Korea and Singapore. There is increase of European countries investment in digital transformation through private and public ICT sector development which usually has positive impact on economic growth as well as key indicators such are GDP, productivity and employment. This paper provides basic review of digital transformation and high-tech sector in Europe as well as comparison between EU and Western Balkan countries. Additionally, there is analysis of influence of ICT spending on GDP growth. Paper could serve as basic for further research in area of influence of tech investment on key macroeconomics indicators.